Changing Rwandan vision of women and land, in the heart of the house, at the outskirts of the world - de Lame, Danielle (Afrika Focus, 1999)
Because the current situation is unstable and the countryside is out of reach, it is impossible to assess in what measures and ways the fact that many women carry the daily burden alone will affect, more generally, the views about gender and gender roles. Women can, indeed keep working in the name of their dead or disappeared husbands; still bearing in mind the old ideology of a continuity based on fidelity to the family ancestors. The disillusions about the further reaching effects on local communities, society, and nation, of beliefs related to the ritual gender complementarity will probably result in a yet more individualized vision of the family. It is realistic to suppose that the rising generation of women would have other views about their own rights, and be less submissive to men if they were, by law, recognized as equal to them on all grounds. This was, however, far from achieved before the genocide, even after the reform of the law which put daughters at an equal footing with sons as far as succession to land rights was concerned. The fact that a majority of households are now female-headed is no, in itself, a guarantee against oppression. If, then, gender roles remain perceived as unchanged, a majority of women will be oppressed in a very crude manner, that is to say, with very little "moral" justification of their exploitation. It also remains to be seen what kind of negotiation the peasant women will be able to achieve with those in power, either male or female. The hope for change rests with active efforts at providing women who are said to be 70% of household heads now, with structures giving them sufficient knowledge, efficacy and credit to organize without being patronized. There are examples of such attempts but their success can only be achieved on the basis of a democracy aiming at giving all access to basic rights. The old modes of exploitation and patronage could perfectly become, under the guises of feminism, associated with female cosmopolitanism. Peasant women could well submit themselves to its local bearers, as they would see no other avenues to the wider world and its wealth. Conformity would take its toll again. Nothing much could have improved in their daily lives, even if the old vision of an engendered fertile land has vanished.